Positive Health Beliefs and Blood Pressure Reduction in the DESERVE Study. Issue 9 (5th May 2020) - Goldmann, Emily; Jacoby, Rachelle; Finfer, Erica; Appleton, Noa; Parikh, Nina S.; Roberts, Eric T.; Boden‐Albala, Bernadette
Abstract : Background: There is growing recognition that positive health beliefs may promote blood pressure (BP) reduction, which is critical to stroke prevention but remains a persistent challenge. Yet, studies that examine the association between positive health beliefs and BP among stroke survivors are lacking. Methods and Results: Data came from the DESERVE (Discharge Educational Strategies for Reduction of Vascular Events) study, a randomized controlled trial of a skills‐based behavioral intervention to reduce vascular risk in a multiethnic cohort of 552 transient ischemic attack and mild/moderate stroke patients in New York City. The exposure was perception that people can protect themselves from having a stroke (ie, prevention self‐efficacy) at baseline. The association between systolic BP (SBP) reduction at 12‐month follow‐up and self‐efficacy was examined using linear regression adjusted for key confounders, overall and stratified by age, sex, race/ethnicity, and intervention trial arm. Approximately three quarters endorsed self‐efficacy. These participants had, on average, 5.6 mm Hg greater SBP reduction compared with those who did not endorse it (95% CI, 0.5–10.7 mm Hg; P =0.032). Self‐efficacy was significantly associated with greater SBP reduction, particularly among female versus male, younger versus older, and Hispanic versus non‐Hispanic white patients. Sensitivity analysis adjusting for baseline SBP instead of elevated BP yielded no association between self‐efficacy and SBP reduction, but showed sex differences in this association (women: β=5.3; 95% CI, −0.2 to 10.8; P =0.057; men: β=−3.3; 95% CI, −9.4 to 2.9; P =0.300; interaction P =0.064). Conclusions: Self‐efficacy was linked with greater SBP reduction among female stroke survivors. Targeted strategies to improve health beliefs after stroke may be important for risk factor management. REGISTRATION: URL: https://www.clini​caltr​ials.gov ; Unique identifier: NCT01836354.